Subject infinitives in Turkish - Göksu, Duygu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
In Turkish, -mA(K) is the nominalizer that forms embedded infinitival clauses. This thesis focuses on the structure of infinitives that are built with this nominalizer and appear to be clausal subjects. The data consist of three sets with the following structures: i) no-control nominalized clauses, ii) control constructions, and iii) passivized embedded clauses. Firstly, the mechanism behind only certain nominalizers’ promotion to subject position in transitive predicates is examined and attributed to the theta hierarchy (see Pesetsky, 1995) and theta role-nominalizer compatibility. Secondly, the type and the means of the control relation observed in subject clauses are analyzed and, contra Boeckx, Hornstein and Nunes (2010), proposed to be logophoric center-based Non-obligatory control. Unlike the English equivalents of these structures examined in Landau (2013), topicality is not enough to build this control relationship. Lastly, the passive constructions that can be built by a group of verbs including başla- ‘to start’, iste- ‘to want’, karar ver- ‘to decide’, çalış/uğraş- ‘to try’, and kalkış- ‘to attempt’ are examined and argued to be voice restructuring configurations (see Wurmbrand 2001 et seq.). Thus, it is concluded that such nominalized passives do not constitute infinitival subjects.
Keywords: Turkish language.; Paradigm (Linguistics); Grammar, Comparative and general -- Infinitive.